The absolute artist : the historiography of a concept - Soussloff, Catherine M. (Minneapolis, Minn. : University of Minnesota Press, 1997)
- On the threshold of historiography: biography, artists, genre##- The artist in nature: Renaissance biography##- The artist in culture: Kulturwissenschaft from Burckhardt to Warburg##- The artist in history: the Viennese school of art history##- The artist in myth: early psychoanalysis and art history##- The artist in the text: rhetorics in the myth of the artist.
Includes bibliographical references (p. 159-193) and index.
boek